Students' perceptions and motivation on the physical therapy profession their relation to academic performance - Garcia-Safra, Sheila Arelli B.
The Physical Therapy profession has been in existence in the Philippines for more than three decades. Unfortunately, it has not clearly established its professional identity. Even students taking up the program do not have a clear understanding of what would be their future profession. This study described the perceptions of students about PT profession then compared them across year levels. It also determined factors influencing students' perception, their preference in terms of career options and correlations between students' perception of the profession, motivation and academic performance. Students from 1st to 4th year were included in this correlation study. Data were generated through a questionnaire. Pearson correlation coefficients were computed to establish significant correlations between students' perception score, motivation and academic performance. Level of significance was set at p<0.05. Perception of the students about the profession and decision in taking up the course were greatly influenced by the parents. Students took up PT because they wanted it to be their pre-medicine course as they wanted the opportunity of working abroad. Most common misconceptions among the students were that physical therapists perform general massage, apply reflexology principles and diagnose patients' disease. Cancer patients and pregnant women were last perceived as possible clients. Reflexology clinics, sauna baths and massage parlors were wrongly perceived as acceptable places of work for physical therapists. Students' perception of the profession varied across year levels and became better as the year level increased. Some constructs on student motivation were correlated with the students' perception of the course. There was no correlation between students' perception of the profession and motivation with academic performance. The study showed that students did not have a clear understanding of the profession even if they are already enrolled in the PT program. Variation in students' perception of the profession across year levels might be expected due to the professional socialization that occurred as the students progressed through the program. However, better understanding of the profession even before the student starts with the program may form a vital role for their motivation in pursuing their studies, finishing the course and practicing their profession.